Synonymy of Orthomus susanae Serrano & Borges, 2009 with Orthomus annae (Donabauer, 2008) (Coleoptera: Carabidae) - Serrano, Artur R.m.; Aguiar, Carlos A.s.; Boieiro, Mário; Borges, Paulo A.v.; Rego, Carla; Amorim, Isabel R.; Ribeiro, Sérvio P.; Pereira, Fernando (Zootaxa, 2012)
Knowledge of the biodiversity of Madeiran islands has for long attracted entomologists in search of new, rare or biologically interesting beetle species. During the XIXth century, Trevor Wollaston extensively sampled the Madeiran islands, compiling a list of almost 700 beetle species, many of them new to science and described by him (e.g., Wollaston 1854, 1865). Thus, for many decades it was thought that the inventory of Madeiran beetle diversity was complete (Machado 2006, but see Lobo & Borges 2010). However, particularly in recent decades, a number of beetle species (most of them of small size and from groups taxonomically more difficult) have been described (see a complete list in Borges et al. 2008b) and important taxonomic revisions have also been made incorporating critical analysis by taxonomic experts. For these reasons, it was as a surprise to find a medium-size and yet undescribed ground beetle species following an extensive survey of epigean arthropods occurring in Madeiran laurel forest fragments. The new species was described in a generic revision of Madeiran Orthomus Chaudoir, 1838 submitted to Zootaxa (Serrano et al. 2009) and the species was included in the comprehensive list of Madeiran terrestrial biodiversity (Borges et al. 2008a), a reference publication on Madeiran fauna and flora published in May 2008. This book also presented a chapter where the distribution of the new species was modelled using predictive distribution models (Jiménez-Valverde et al. 2008).